2019
DOI: 10.1080/09603123.2019.1657075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment plant management on human health and ecological risks from wastewater irrigation in developing countries – case studies from Cochabamba, Bolivia

Abstract: Wastewater irrigation is a common practice in developing countries due to water scarcity and increasing demand for food production. However, there are health risks and ecological risks associated with this practice. Small-scale wastewater treatment plants (WWTPs) intend to decrease these risks but still face management challenges. This study assessed how the management status of five small-scale WWTPs in Cochabamba, Bolivia affects health risks associated with consumption of lettuce and ecological risks due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To address this issue the main problems of LICs include lack of fresh water for irrigation of crops and resources for wastewater treatment. Additionally, lack of education and human awareness campaigns on problems, such as crop risk and regulatory updating and implementation of laws aimed at wastewater management (Khalid et al, 2018;Cossio et al, 2019). Among the negative effects of irrigating with contaminated water in agricultural crops include increased concentration of HMs.…”
Section: )mentioning
confidence: 99%
“…To address this issue the main problems of LICs include lack of fresh water for irrigation of crops and resources for wastewater treatment. Additionally, lack of education and human awareness campaigns on problems, such as crop risk and regulatory updating and implementation of laws aimed at wastewater management (Khalid et al, 2018;Cossio et al, 2019). Among the negative effects of irrigating with contaminated water in agricultural crops include increased concentration of HMs.…”
Section: )mentioning
confidence: 99%
“…The authors found that heavy metal concentrations in the effluent and in the vegetables were within the recommended range for irrigation and WHO-permissible limits for daily tolerable heavy metal intake, respectively, and that the WRRF was efficient. Case studies in Cochabamba, Bolivia, showed that better management of the WRRF operation and maintenance could reduce microbial risk levels to acceptable levels and reduce ANNUAL LITERATURE REVIEW ecological risks from nitrogen and phosphorous accumulation in soil when reusing wastewater for irrigation practices (Cossio et al, 2019). Xu, de Koning, and Geng (2019) investigated the reliability and efficiency of continuous sand filtration-multimedia filtration (CSF-MMF) followed by UF and RO for the reclamation of effluent from a WRRF for surface water supplementation and greenhouse irrigation water.…”
Section: Case Studiesmentioning
confidence: 99%
“…The authors found that heavy metal concentrations in the effluent and in the vegetables were within the recommended range for irrigation and WHO‐permissible limits for daily tolerable heavy metal intake, respectively, and that the WRRF was efficient. Case studies in Cochabamba, Bolivia, showed that better management of the WRRF operation and maintenance could reduce microbial risk levels to acceptable levels and reduce ecological risks from nitrogen and phosphorous accumulation in soil when reusing wastewater for irrigation practices (Cossio et al, 2019).…”
Section: Case Studiesmentioning
confidence: 99%
“…The UW treatment aims to avoid damage to public, private, and industrial water supplies, to water intended for recreation, fishing activities, agriculture, and also depreciation of the value of the land and impacts on the ecosystems and human health (Cossio et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%